Assessing Trust in a Classroom Environment, applying Social Network Analysis - Kuz, Antonieta (2016)
This paper builds the study of social networks and their bonds with trust, through the methods of detection and description of structural properties. Networks of relationships can be mapped and managed to enhance organizational learning. Social Network Analysis (SNA) is detecting and interpreting patterns of social ties among actors. Due to trust is a crucial factor among the interaction between actors, we use NodeXL© tool to perform a case study in a classroom environment. We relate the trust measures to the clustering coefficient, centrality, and strong and weak ties which are computable characteristics of a social network. We find that more connected classes, and classes with stronger friendship relationships, enjoy more trust.